Justificando intervenções: a política externa norte-americana e a América Latina - Merendi, Izaura Peghim (2007)
This study aims to demonstrate that the United States of America have always tried to dissimulate their interventions in Latin America. Ever since the independence of Latin-American colonies, the U.S. have been trying to justify their expansionism in the region. To the end of the Cold War , the interventions were justified by the rhetoric of the contention of external threatens European recolonization and Soviet communism with the end of the bipolar conflict, the domination has won a new justification, i. e., the necessity of keeping the order and promote democracy. Thus, hegemony began to be exerted through the North-American capacity of imposing its values democracy and free trade in the region.